Sensitivity analysis of temporal parameters in a dynamic LCA framework - Shimako, Allan Hayato; Tiruta-Barna, Ligia; Bisinella de Faria, Ana Barbara; Ahmadi, Aras; Spérandio, Mathieu (The Science of the total environment, 2018)
Including the temporal dimension in the Life Cycle Assessment (LCA) method is a very recent research subject. A complete framework including dynamic Life Cycle Inventory (LCI) and dynamic Life Cycle Impact Assessment (LCIA) was proposed with the possibility to calculate temporal deployment of climate change and ecotoxicity/toxicity indicators. However, the influence of different temporal parameters involved in the new dynamic method was not still evaluated. In the new framework, LCI and LCIA results are obtained as discrete values in function of time (vectors and matrices). The objective of this study is to evaluate the influence of the temporal profile of the dynamic LCI and calculation time span (or time horizon in conventional LCA) on the final LCA results. Additionally, the influence of the time step used for the impact dynamic model resolution was analysed. The range of variation of the different time steps was from 0.5day to 1year. The graphical representation of the dynamic LCA results shown important features such as the period in time and the intensity of the worst or relevant impact values. The use of a fixed time horizon as in conventional LCA does not allow the proper consideration of essential information especially for time periods encompassing the life time of the studied system. Regarding the different time step sizes used for the dynamic LCI definition, they did not have important influence on the dynamic climate change results. At the contrary, the dynamic ecotoxicity and human toxicity impacts were strongly affected by this parameter. Similarly, the time step for impact dynamic model resolution had no influence on climate change calculation (step size up to 1year was supported), while the toxicity model resolution requires adaptive time step definition with maximum size of 0.5day. [Display omitted] •Dynamic LCA framework interconnects temporal inventory and dynamic impact models.•Dynamic climate change is not sensitive to LCI time steps lower than 1year.•Dynamic (eco)toxicity indicators are very sensitive to LCI temporal definition.•A predefined time horizon has no interest and relevance for dynamic LCA models.